Global microRNA profiling of metastatic conjunctival melanoma. Issue 5 (October 2019) - Mikkelsen, Lauge H.; Andersen, Mette K.; Andreasen, Simon; Larsen, Ann-Cathrine; Tan, Qihua; Toft, Peter B.; Wadt, Karin; Heegaard, Steffen
Abstract : This study aimed to investigate the microRNA (miRNA) profile in primary tumors from conjunctival melanoma with and without subsequent metastatic spread along with their coupled distant metastases to identify miRNAs likely to be involved in metastatic progression. This observational study included 13 patients with metastatic conjunctival melanoma (follow-up: 1–39 years) treated at a Danish referral center. Twenty-five patients with nonmetastatic conjunctival melanoma (follow-up: 5–17 years) were included for comparison. Global miRNA profiling was performed with the Affymetrix GeneChip 4.1 microarray. Taqman qPCR arrays were used for validation. Significant differentially expressed miRNAs were defined as having a false discovery rate of less than 0.05. Primary conjunctival melanoma with and without subsequent metastatic spread clustered separately according to miRNA expression, and 15 miRNAs were found to have significant differential expression. Six miRNAs (hsa-miR-4528, hsa-miR-1270, hsa-miR-1290, hsa-mir-548f-4, hsa-mir-4278, and hsa-miR-34a-3p) were downregulated and nine miRNAs were upregulated (hsa-mir-575, hsa-miR-527, hsa-miR-518a-5p, hsa-miR-6759-5p, hsa-miR-8078, hsa-mir-4501, hsa-mir-622, hsa-mir-4698, and hsa-mir-4654) in primary conjunctival melanoma with subsequent metastatic spread. A comparison of primary conjunctival melanoma with their pair-matched metastases identified six significant differentially expressed miRNAs (hsa-miR-1246 and hsa-miR-302d-5p, hsa-mir-6084, hsa-miR-184, hsa-mir-658, and hsa-mir-4427). qPCR confirmed downregulation of hsa-miR-184 in the distant metastases when compared with the corresponding primary tumor. Primary conjunctival melanoma with and without subsequent metastatic spread separated clearly on the miRNA level when profiled with microarray-based methods. qPCR was able to replicate expression levels of one miRNA (hsa-miR-184) that was downregulated in metastases when compared with corresponding primary tumors. Abstract : Supplemental Digital Content is available in the text.